Serum matrix metalloproteinase 7 as a diagnostic and prognostic biomarker for extrahepatic biliary atresia - Teg Rabab Singh; Prabudh Goel; Minu Bajpai; Devasenathipathy Kandasamy; Rohan Malik; Rajni Yadav; Shyam Prakash; Kalaivani Mani; Madhavi Tripathi; Devendra Kumar Yadav; Anjan Kumar Dhua; Vishesh Jain; et al. (Wolters Kluwer Medknow Publications, 2022)
Background: Differentiation of neonatal cholestasis into neonatal hepatitis (NH) and extrahepatic biliary atresia (EHBA) is essential to formulate the treatment plan; promptness is indispensable for optimal outcomes. The clinical and nonoperative algorithms lack precision; the gold standard investigations (liver biopsy or per-operative cholangiogram) are invasive. There is a need for a noninvasive test which is both, sensitive and specific and has a high likelihood ratio. Aim: To study the (diagnostic) role of matrix metalloproteinase 7 (MMP-7) as a serum biomarker to differentiate between EHBA and NH and evaluate the prognostic significance in EHBA based on its correlation with liver histopathology and serological predictors of liver fibrosis - Aspartate-to-Platelet Ratio Index (APRI) and Fibrosis-4 (FIB-4). Materials and Methods: This was a prospective study conducted upon patients of neonatal cholestasis presenting with acholic stools (n = 46) with equal number of controls (n = 45) with no liver pathology. Observational parametric included disease-specific workup and serum MMP-7 levels (all participants); liver biopsyl and APRI-FIB-4 (EHBA). Results: (Diagnostic) Serum MMP-7 levels were significantly elevated in EHBA (n = 25; 28 ng/mL) as compared to those in NH (n = 21; 1.88 ng/mL) and normal infants (n = 45; 1.2 ng/mL) (P < 0.001 for both). Serum cutoff at 4.99 ng/mL differentiated EHBA-NH with a high sensitivity (96%), specificity (90.5%), and a negative predictive value (95%), with the number needed to misdiagnose being 23. (Prognostic) Inflammatory activity and fibrosis-stage on liver histopathology (METAVIR-and-Ishak scores) correlated with MMP-7 levels. APRI and FIB-4 scores also depicted a strong correlation with each other, age of the patient, and liver fibrosis. Conclusions: MMP-7 has a diagnostic value in differentiating EHBA from NH and may also be used as a prognostic biomarker in the follow-up of these patients. MMP-7 levels in controls may be used as a baseline for future studies.